The VISCACHA survey – IV. The SMC West Halo in 8D. Issue 3 (14th February 2022) - Dias, B; Parisi, M C; Angelo, M; Maia, F; Oliveira, R A P; Souza, S O; Kerber, L O; Santos, J F C; Pérez-Villegas, A; Sanmartim, D; Quint, B; Fraga, L; et al.
ABSTRACT: The structure of the Small Magellanic Cloud (SMC) is very complex, in particular in the periphery that suffers more from the interactions with the Large Magellanic Cloud (LMC). A wealth of observational evidence has been accumulated revealing tidal tails and bridges made up of gas, stars, and star clusters. Nevertheless, a full picture of the SMC outskirts is only recently starting to emerge with a 6D phase-space map plus age and metallicity using star clusters as tracers. In this work, we continue our analysis of another outer region of the SMC, the so-called West Halo, and combined it with the previously analysed Northern Bridge. We use both structures to define the Bridge and Counter-bridge trailing and leading tidal tails. These two structures are moving away from each other, roughly in the SMC–LMC direction. The West Halo form a ring around the SMC inner regions that goes up to the background of the Northern Bridge shaping an extended layer of the Counter-bridge. Four old Bridge clusters were identified at distances larger than 8 kpc from the SMC centre moving towards the LMC, which is consistent with the SMC–LMC closest distance of 7.5 kpc when the Magellanic Bridge was formed about 150Myr ago; this shows that the Magellanic Bridge was not formed only by pulled gas, but it also removed older stars from the SMC during its formation. We also found age and metallicity radial gradients using projected distances on sky, which are vanished when we use the real 3D distances.